Characteristics and performance of cow manure, pig manure and granular sludge as seeding material in the start-up of UASB reactors - Musico, Yvonne Ligaya F. (2004)
The characteristics and performance of pig manure, cow manure and granular sludge from anaerobic reactor in the start-up of an upflow anaerobic sludge blanket (UASB) were evaluated in this study. Specific methanogenic activity (SMA), settleability total and volatile solid (TS and VS) content of pig manure and cow manure were compared with those of granular sludge to determine if they can be used as alternative seed materials for high rate anaerobic reactors. Seeding materials were fed in laboratory UASB reactor using synthetic sugar containing wastewater. The granular sludge which was obtained from a methanogenic reactor treating brewery wastewater, achieved up to 90% COD removed, almost 75% was converted to methane. The COD removal in the UASB seeded with digested cow manure reached up to 70%. More than 56% of this removed COD was converted to methane. In the UASB seeded with digested pig manure, almost 70% of the influent COD was removed. About 61% of this removed COD was converted to methane. The Asia Brewery sludge has the highest SMA (0.8 gCH4-COD. gVS1.d-1). The SMA values of the digested cow manure and digested pig manure reached up to 0.25 gCH4-COD.gVS-1.d-1 and 0.24 gCH4-COD.gVS-1.d-1, respectively. There was a significant growth of biomass during the 150 days start-up run. All the tested sludge samples have good setting properties. SVI values were below 50 ml.gTS-1. Sludge particles from all three UASB reactors when viewed through scanning election microscope resembled the aggregates of Methanothrix-like microorganisms, which are among the microorganisms to which granule formation is attributed in previous studies.